Comfort based floor design employing tuned inerter mass system. (13th October 2019) - Chen, Qingjun; Zhao, Zhipeng; Xia, Yuying; Pan, Chao; Luo, Hao; Zhang, Ruifu
Abstract: A comfort-based optimal method has been developed for designing floors using tuned inerter mass systems (TIMS) to reduce the vertical-vibration response of floors subjected to human-induced excitations. Acceleration response of the floor and output force of TIMS were first derived via stochastic analysis. Subsequently, variation patterns in acceleration-response and output-force ratios were studied and compared by changing values of TIMS parameters. Based on the results of this parametric investigation, a comfort-based optimal design method and the corresponding procedure to be followed were developed. In the proposed method, the weighted average of the required additional tuned mass and TIMS output force are expected to be minimized whilst realizing the expected level of satisfaction in terms of target comfort performance of the floor structure (i.e., target acceleration response ratio). For different design targets, optimized TIMS parameters can be obtained using the proposed design method, and such design cases have been demonstrated by performing time-history analysis under different external human-induced excitations. Results of the said analysis demonstrate that the proposed design method effectively satisfies comfort-performance objectives of a floor with optimal actual mass through use of an inerter system. In addition, the proposed method can be used to maintain a balance between the control cost, additional tuned mass, and structural comfort performance.